Colleges and schools-College of Arts and Humanities-Music-0050
Fresno-Madera counties All course Honor High School Orchestra FSC Auditorium Dec. 12, 1953 Mary Lou Nevins, Concert mistress Dave Kichbiehl-Horn, Bill-Tpt, Pauline Shick Slieter-Flute, Reed Adams-Tuba, Smilzer-Tuba, Larry Hock-Trambone, Richard Heay-Bsn